The Role of Service Quality and Trust in Building Customer Satisfaction and Loyalty - Nusjirwan Nusjirwan; Ronal Regen; Rio Nardo (Budapest International Research and Critics University, 2020)
This study aims to understand the role of service quality and trust in developing customer satisfaction and loyalty at JNE Margonda, Depok. The research is used as a quantitative approach. Respondents are 127 people who were taken by purposive sampling technique. This study uses Structural Equation Modeling (SEM) with Lisrel 8.80 applications for analyzing the data. All three hypotheses are accepted, and the data supports the model. H1: service quality has a positive and significant effect on customer satisfaction. H2: Trust has a positive and significant impact on customer satisfaction. H3: Customer satisfaction has a positive and significant effect on customer loyalty. The Conclusion: (1) The high quality of service from JNE Surabaya increases customer satisfaction (2) If trust in JNE Surabaya is high, then higher customer satisfaction will be higher too; (3) Respondents who feel satisfied when using JNE Margonda services will be more loyal to JNE Surabaya.